ANALISIS PENGARUH LINGKUNGAN KERJA FISIK, PENGHARGAAN, DAN KARAKTERISTIK PEKERJAAN TERHADAP KOMITMEN ORGANISASI (Kasus Pada Karyawan Hotel Grasia Semarang) - Firdhaus, Olwan Zakki; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to examine and analyze the effect of physical work environment, reward, and job characteristics on employees organization commitment of Hotel Grasia Semarang. Employee turnover data for Hotel Grasia over the past four years shows that the turnover rate is said to be unhealthy - on average, eight employees remain out of work. This data may indicate an employee organization commitment issue at Hotel Grasia. Therefore, Hotel Grasia must increase its employees' organizational commitment by taking into account the influencing variables such as those of Richard Steers (in Hadiyani, 2013) ie work environment, job characteristics, and organization as a whole including work rewards.Questionnaires were distributed to 105 employees with total sampling method. This research used software SPSS Statistic 23. The technique of data testing includes validity test, reliability test, classical assumption test, t test, F test, coefficient determination, and multiple linear regression analysis.The results of this research indicate that physical work environment has positive and significant effect on employees organization commitment, reward has positive and significant impact on employees organization commitment, and job characteristic has positive and significant impact to employees organization commitment.